2018
DOI: 10.1093/jncics/pky067
|View full text |Cite
|
Sign up to set email alerts
|

The WISDOM Personalized Breast Cancer Screening Trial: Simulation Study to Assess Potential Bias and Analytic Approaches

Abstract: Background WISDOM (Women Informed to Screen Depending on Measures of Risk) is a randomized trial to assess whether personalized breast cancer screening—where women are screened biannually, annually, biennially, or not at all depending on risk and age—can prevent as many advanced (stage IIB or higher) cancers as annual screening in women ages 40–74 years across 5 years of trial time. The short study time in combination with design choices of not requiring study entry and exit mammograms for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In particular, using the recent extension of the BOADICEA model, it has been demonstrated that the 313-SNP PRS provides greater level of risk stratification in the population than epidemiological risk factors alone, and that the greatest level of risk stratification is achieved when both the PRS and epidemiological risk factors are considered jointly 10 . Screening trials 11 – 13 in women of predominantly European descent are ongoing to evaluate personalised breast cancer screening programme based on a woman’s individual risk of disease, as a means of improving screening efficiency 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, using the recent extension of the BOADICEA model, it has been demonstrated that the 313-SNP PRS provides greater level of risk stratification in the population than epidemiological risk factors alone, and that the greatest level of risk stratification is achieved when both the PRS and epidemiological risk factors are considered jointly 10 . Screening trials 11 – 13 in women of predominantly European descent are ongoing to evaluate personalised breast cancer screening programme based on a woman’s individual risk of disease, as a means of improving screening efficiency 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Mammographers' acceptance of MammoRisk® for evaluating BC risk in the clinical setting is high [42] and the model is being increasingly used with training as part of the ambitious European clinical trial MyPeBS [29]. The primary objective of the MyPeBS study is the same as that of the WISDOM study conducted in the United States [43]: to evaluate the impact of personalized BC screening on the rate of diagnosis of BC stage 2B in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective clinical trial would provide more functional and extended evaluation of the performance of ML algorithms, and findings can be compared with ongoing personalised breast cancer screening trials like 'My PeBS' and 'WISDOM'. 54,55…”
Section: Strengths and Limitationsmentioning
confidence: 99%